2020
DOI: 10.31557/apjcp.2020.21.7.2055
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immunoglobulins as Diagnostic Markers in Smokeless Tobacco Users for Prevention of Oral Potentially Malignant Disorders

Abstract: Background: Smokeless tobacco (SLT) remains a threat amongst a large population across the globe and particularly in India. Among the 28 known carcinogens in SLT, tobacco-specific nitrosamines are considered to be the most potent and it has been shown to cause immunomodulatory effects making the individual susceptible to various diseases. Immunoglobulins (Ig) form the defense against pathogens at the mucosal surfaces and SLT might interfere with its production and function. Therefore, the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Oral mucosal inflammation is a major component in the pathophysiology of OSF, and the inflammatory site is where immune cytokines are produced, including interleukin, tumor necrosis factor, interferon, and transforming growth factor [19][20][21]. Researchers also found that people with OSF had considerably higher serum levels of immunoglobulin IgG and IgA [22][23][24], indicating the presence of an immunological response to OSF. In the course of clinical diagnosis and treatment, we discovered that there were other factors than local irritants that could cause oral submucosal fibrosis, such as betel chewing, smoking, drinking, and eating spicy foods.…”
Section: Discussionmentioning
confidence: 99%
“…Oral mucosal inflammation is a major component in the pathophysiology of OSF, and the inflammatory site is where immune cytokines are produced, including interleukin, tumor necrosis factor, interferon, and transforming growth factor [19][20][21]. Researchers also found that people with OSF had considerably higher serum levels of immunoglobulin IgG and IgA [22][23][24], indicating the presence of an immunological response to OSF. In the course of clinical diagnosis and treatment, we discovered that there were other factors than local irritants that could cause oral submucosal fibrosis, such as betel chewing, smoking, drinking, and eating spicy foods.…”
Section: Discussionmentioning
confidence: 99%